2020
DOI: 10.1038/s41598-020-78252-y
|View full text |Cite
|
Sign up to set email alerts
|

A computational model of language functions in flexible goal-directed behaviour

Abstract: The function of language in high-order goal-directed human cognition is an important topic at the centre of current debates. Experimental evidence shows that inner speech, representing a self-directed form of language, empowers cognitive processes such as working memory, perception, categorization, and executive functions. Here we study the relations between inner speech and processes like feedback processing and cognitive flexibility. To this aim we propose a computational model that controls an artificial ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 66 publications
2
35
0
Order By: Relevance
“…We adopted the same procedure corroborated in [6] to execute the parameters search, aimed to find the parameters of the models that produce the behaviour that best fits those of human populations. In particular we randomly-sampled 3, 000 combinations of parameters each drawn with a uniform distribution in the following ranges: φ: (0.0, 1.0); µ: (0.0, 1.0); τ : (0.0, 0.3); λ: (0.0, 1.0).…”
Section: Fitting Results and Comparison Between The Behaviour Of The Models And Of Human Groups: Models Validation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…We adopted the same procedure corroborated in [6] to execute the parameters search, aimed to find the parameters of the models that produce the behaviour that best fits those of human populations. In particular we randomly-sampled 3, 000 combinations of parameters each drawn with a uniform distribution in the following ranges: φ: (0.0, 1.0); µ: (0.0, 1.0); τ : (0.0, 0.3); λ: (0.0, 1.0).…”
Section: Fitting Results and Comparison Between The Behaviour Of The Models And Of Human Groups: Models Validation Detailsmentioning
confidence: 99%
“…Evidence has shown that inner speech plays an important role in supporting cognition. In particular, it boosts categorisation processes [2,3], executive functions [4,5,6], working memory [7], metacognition [8], and motivation [9]. Several experimental and clinical studies started to investigate the role of inner speech in psychiatric and neurodiversity conditions (for a recent review, see [10]).…”
Section: Introductionmentioning
confidence: 99%
“…An updated version of the model was enhanced with the addition of an inner speech component and was validated in [6]. The model reproduced a complete behavioural profile (WCST indices) of three groups of teenagers in different experimental conditions: control, motor tapping and verbal tapping.…”
Section: Modelmentioning
confidence: 99%
“…These components support the cognitive functions needed to perform the task in a goal-directed manner. We reported the computational details of the model in Supplementary Materials and a throughout analysis of the model computational architecture and dynamics is presented in [6].…”
Section: Modelmentioning
confidence: 99%
See 1 more Smart Citation